Consequences of Repression of Emotion: Physical Health, Mental Health and General Well Being - Jainish Patel; Prittesh Patel (International Journal of Psychotherapy Practice and Research, 2019)
The widely held belief that emotional and psychological processes affect our physical health, mental health and general well-being are central to a holistic view of the individual, and as such, it is a useful foundational concept in integrative medicine. The purpose of this paper is to review substantial amounts of the latest research and recent findings on this issue to enable us to throw some light on how inhibitory factors to emotional expression and experience can endanger our health, both physically and psychologically including our general wellbeing. In addition, the connection between repression of emotion and certain mental disorders like depression and scientifically proven healthy ways to manage issues bordering on emotion was outlined. The information contained in this paper is just as important to health care providers and also to the patients they deal with
Keywords: Emotion